1998
DOI: 10.1007/s002130050722
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cigarette smoking and 12-h abstention on working memory during a serial-probe recognition task

Abstract: Nicotine has been shown to affect attentional and mnemonic processes. However, whether these effects are due to changes in perceptual and/or motor aspects of the tasks is not at all clear. This study tested the hypothesis that nicotine from cigarette smoking has differential effects on perceptual and motor processes, as reflected by event-related potentials (ERPs) and reaction times (RTs), respectively, and that perceptual effects may be specific to changes in working memory. ERPs. RTs and performance accuracy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 56 publications
4
30
0
Order By: Relevance
“…Philips and Fox (1998) found that subjects who chewed nicotine gum showed improved recollection in specific short-term memory tasks. Similar benefits were found by Pineda et al (1998) who concluded that smoking a cigarette may improve recall ability in habitual smokers by optimizing the chohnergic pathways involved in some memory processes. Wesnes et al (1983) reported that rapid information processing was improved after subjects smoked nicotine-containing cigarettes compared to placebo cigarettes.…”
Section: The Views Expressed In Tffls Article Are Those Of the Authorsupporting
confidence: 75%
“…Philips and Fox (1998) found that subjects who chewed nicotine gum showed improved recollection in specific short-term memory tasks. Similar benefits were found by Pineda et al (1998) who concluded that smoking a cigarette may improve recall ability in habitual smokers by optimizing the chohnergic pathways involved in some memory processes. Wesnes et al (1983) reported that rapid information processing was improved after subjects smoked nicotine-containing cigarettes compared to placebo cigarettes.…”
Section: The Views Expressed In Tffls Article Are Those Of the Authorsupporting
confidence: 75%
“…Nevertheless, the present study cannot distinguish deficits in working memory that preceded nicotine dependence from those that may be attributable to chronic nicotine exposure. Impaired memory performance, as seen here, is surprising in view of the reported improvement in memory performance in animals chronically exposed to nicotine (Attaway et al 1999;Levin et al 1997) and in humans (Perkins et al 1994;Pineda et al 1998). However, this finding is consistent with reports of impaired performance on complex information-processing tasks in chronic smokers, independent of nicotine withdrawal or smoking abstinence (Spilich et al 1992).…”
Section: Discusssionmentioning
confidence: 46%
“…Performance decrements were more severe with earlier age at the onset of smoking. In adult humans, cessation of regular tobacco smoking disrupts memory (Pineda et al, 1998;West and Hack, 1991) and attention (Shiffman et al, 1995;Snyder et al, 1989), while administration of nicotine, or resumption of tobacco smoking, reverses these withdrawal-related deficits (Foulds et al, 1996;Krebs et al, 1994;Pineda et al, 1998). Consistent with these observations in adults, memory deficits worsened in adolescent tobacco smokers during nicotine withdrawal (Jacobsen et al, 2005).…”
Section: Introductionmentioning
confidence: 60%